Positive family history of premature coronary artery disease and long-term mortality in patients undergoing conventional coronary angiography. The ECAD registry. (14th October 2021) - Karout, M; Dykun, I; Hendricks, S; Balcer, B; Al-Rashid, F; Totzeck, M; Rassaf, T; Mahabadi, A A
Abstract: Background: The clinical value of positive family history of premature coronary artery disease (CAD) in risk prediction of cardiovascular diseases is controversial. While an association with risk factors and disease manifestation has been described in observational studies, it is not implemented in clinically established risk algorithms. Purpose: We evaluated the association of positive family history of premature CAD with cardiovascular risk factors, presence of obstructive CAD, and long-term mortality. Methods: The present analysis is based on the ECAD registry of patients undergoing invasive coronary angiography at the Department of Cardiology and Vascular Medicine at the University Clinic Essen between 2004 and 2019. For this analysis, we excluded all patients with missing follow-up information. Self-reported family history of premature CAD was categorized as positive, negative, or unknown. Baseline characteristics and presence of obstructive CAD were compared between patient with and without positive family history. Cox regression analysis was used to determine the association of positive family history with morality. Results: Overall, data from 33, 865 patient admissions (mean age: 65.0±13.1 years, 69% male) were included. Positive family history was present in 4, 995 (14.8%) patients, negative family history in 17, 806 patients (52.6%), while family history of premature CAD was unknown in 11, 064 (32.7%) patients. Patients with positive family history were significantly younger (63.6±12.4 vs. 65.9±13.3 years, p<0.0001), more frequently had diabetes (11.4 vs. 9.3%, p<0.0001), and more frequently were active smokers (23.5 vs. 13.8%, p<0.0001). Obstructive CAD with need for revascularization therapy was more frequently present in patients with positive family history (36.2 vs. 30.2%, p<0.0001), while highest rate of obstructive CAD was observed in patients without known status regarding family history (37.9%, p<0.0001). In multivariable Cox regression analysis, known positive family history as compared to no family history of premature CAD was associated with best long-term survival (hazard ratio [95% confidence interval]: 0.65 [0.59–0.70], p<0.0001), while slightly higher mortality was observed for patients with unknown status (1.14 [1.08–1.21], p<0.0001). Kaplan-Meier analysis revealed, that patients with unknown family status regarding premature disease had worst short to intermediate-term survival (figure 1). Conclusion: Positive family history of premature CAD is associated with younger age, higher rates of smoking and diabetes, and higher frequency of obstructive coronary artery disease, while long-term survival was improved as compared to patients without family history of premature CAD. In contrast, patients with unknown status regarding family history of CAD seem to represent a heterogeneous cohort and may qualify for intensified workup, as they have highest rates of obstructive CAD and poorest short- to intermediate survival. Funding Acknowledgement: Type of funding sources: None.